Evaluating the Accuracy of Tibial Tunnel Placement After Anatomic Single-Bundle Anterior Cruciate Ligament Reconstruction. Issue 13 (November 2019) - Pedneault, Christopher; Laverdière, Carl; Hart, Adam; Boily, Mathieu; Burman, Mark; Martineau, Paul A.
Background: Anatomic anterior cruciate ligament (ACL) reconstruction improves knee kinematics and joint stability in symptomatic patients who have ACL deficiency. Despite a concerted effort to place the graft within the ACL's native attachment sites, the accuracy of tunnel placement using contemporary techniques is not well established. Purpose: To use 3-dimensional magnetic resonance imaging (3D MRI) to prospectively evaluate the accuracy of tibial tunnel placement after anatomic ACL reconstruction. Study Design: Case series; Level of evidence, 4. Methods: Forty patients with symptomatic, ACL-deficient knees were prospectively enrolled in the study and underwent 3D MRI of both their injured and uninjured knees before and after surgery through use of a validated imaging protocol. The root ligament of the anterior horn of the lateral meniscus was used as a radiographic reference, and the center of the reconstructed graft was compared with that of the contralateral normal knee. The tunnel angles and intra-articular graft angles were also measured, as was the percentage overlap between the native tibial footprint and tibial tunnel. Results: The reconstructed tibial footprint was placed at a mean ± SD of 2.14 ± 2.45 mm ( P < .001) medial and 5.11 ± 3.57 mm ( P < .001) posterior to the native ACL footprint. The mean distance between the center of the native and reconstructed ACL at the tibial attachment site was 6.24 mm. Of the 40 patients, 18 patients had a tibial tunnel that overlapped more than 50% of the native footprint, and 10 patients had maximal (100%) overlap. Further, 22 of the 40 patients had less than 50% overlap with the native footprint, and in 12 patients the footprint was missing completely. Conclusion: Despite the use of contemporary surgical techniques to perform anatomic ACL reconstruction, a significant positioning error in tibial tunnel placement remains.